2011
DOI: 10.1161/atvbaha.110.219238
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nox4 NADPH Oxidase Enhances Vasodilatation and Reduces Blood Pressure In Vivo

Abstract: Objective-Increased reactive oxygen species (ROS) production is involved in the pathophysiology of endothelial dysfunction. NADPH oxidase-4 (Nox4) is a ROS-generating enzyme expressed in the endothelium, levels of which increase in pathological settings. Key Words: blood pressure Ⅲ endothelial function Ⅲ reactive oxygen species Ⅲ vasodilation Ⅲ NADPH oxidase E ndothelial dysfunction, in particular the impairment of endothelium-dependent vasodilatation, is involved in the pathophysiology of hypertension and ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
229
3
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(247 citation statements)
references
References 37 publications
11
229
3
4
Order By: Relevance
“…Deletion of either Nox4 or -2 in STZ-induced diabetes is not beneficial and may even be deleterious in the case of Nox4, supporting studies showing that Nox4 may play a protective role in chronic kidney injury and endothelial dysfunction. [43][44][45][46] However, the role of Nox4 remains controversial in the diabetic setting, because short-term pharmacological Nox4 inhibition reduces renal ROS generation, glomerular hypertrophy, and fibronectin expression. 42 Unlike other Nox family members, nothing is known regarding the function of Nox5 in animal models of disease, owing mainly to its absence from the mouse and rat genome.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of either Nox4 or -2 in STZ-induced diabetes is not beneficial and may even be deleterious in the case of Nox4, supporting studies showing that Nox4 may play a protective role in chronic kidney injury and endothelial dysfunction. [43][44][45][46] However, the role of Nox4 remains controversial in the diabetic setting, because short-term pharmacological Nox4 inhibition reduces renal ROS generation, glomerular hypertrophy, and fibronectin expression. 42 Unlike other Nox family members, nothing is known regarding the function of Nox5 in animal models of disease, owing mainly to its absence from the mouse and rat genome.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that Nox4 may actually have protective effects, possibly through Nox4-derived H 2 O 2 , which may act as a vasodilator in some vascular beds (164,238). This could explain why mice with targeted endothelial Nox4 overexpression have lower blood pressure and improved endothelium-dependent vasodilation versus wild-type controls (164).…”
Section: Nox4mentioning
confidence: 99%
“…Redox Signal. 20,[164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182] …”
Section: Introductionunclassified
“…In disease states, it is well established that elevated expression and activity of NADPH oxidase isoforms in the vasculature, together with the resulting increased ROS production, contribute to the initiation and maintenance of the atherosclerotic process. However, it should be noted that recent studies have unveiled a distinct, potentially beneficial role for the Rac1-independent Nox4 isoform in the vascular wall, by enhancing vasodilation in a H 2 O 2 -mediated way (91), underlying the fact that controlled ROS production in specific cellular compartments may be beneficial for vascular homeostasis, as they serve as signaling molecules that mediate multiple biological processes.…”
Section: Fig 4 Effects Of Statins On Enos In Ecsmentioning
confidence: 99%